On the Derivatives of Bernstein Polynomials: An Application for the Solution of High Even-Order Differential Equations. (15th March 2011) - Doha, E. H.; Bhrawy, A. H.; Saker, M. A.
Abstract : A new formula expressing explicitly the derivatives of Bernstein polynomials of any degree and for any order in terms of Bernstein polynomials themselves is proved, and a formula expressing the Bernstein coefficients of the general-order derivative of a differentiable function in terms of its Bernstein coefficients is deduced. An application of how to use Bernstein polynomials for solving high even-order differential equations by Bernstein Galerkin and Bernstein Petrov-Galerkin methods is described. These two methods are then tested on examples and compared with other methods. It is shown that the presented methods yield better results.